Characterization method for mechanical strength of powdery porous material and application of characterization method

By applying pressure to the powdered porous material and removing pressure to measure the specific surface area change rate and calculating the specific surface modulus, the problem that the prior art cannot quantify the mechanical strength of the powdered porous material is solved, and a rapid evaluation of the cycle stability of lithium battery materials is achieved.

CN119643432APending Publication Date: 2025-03-18XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411878676.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art cannot directly and effectively quantify the mechanical strength of powdered porous materials, especially when used in lithium-ion batteries, and it is difficult to evaluate the ability of the material to resist rolling stress and expansion stress.

Method used

By applying pressure to the powdery porous material, the specific surface area change rate of the material is measured, and the specific surface modulus is calculated to quantify the mechanical strength of the material. This method is suitable for rapid evaluation of the cycle stability of lithium battery powder negative electrode materials.

Benefits of technology

The direct quantification of the mechanical strength of powdered porous materials is achieved, and the cyclic stability of the material can be quickly evaluated in lithium battery applications, simplifying the testing process and improving the accuracy of the test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643432A_ABST
    Figure CN119643432A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and provides a characterization method and application of a powdery porous material. The characterization method comprises the following steps: quantifying the mechanical strength by acquiring the specific surface modulus of the powdery porous material, wherein the specific surface modulus is calculated according to the following formulas: gamma (p) = p / epsilon (p) and epsilon (p) = S (p)-S (p0) / S (p0). The characterization method is simple to operate, and the material does not need to be prepared into a corresponding finished product to test the performance. And the method has important significance in rapidly evaluating the influence of the powdery porous material on the performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, provides a method for characterizing the mechanical strength of a powdery porous material and its application. Background Art

[0002] Mechanical strength refers to the maximum load that a material can withstand per unit area when subjected to external force. High-density alloy materials are often used in high-demand precision industries such as aerospace, national defense, and nuclear industry due to their good buffering properties, high mechanical strength, and excellent comprehensive performance. Engineering plastics with high rigidity and low creep can cope with harsh physical and chemical conditions and can partially replace metal materials in electrical, construction and other industries. The requirements of many industries for the strength of various materials have triggered people's thinking about evaluating mechanical strength. An indicator is needed to distinguish the differences between materials and measure the mechanical properties of materials. The current mechanical strength test method is based on mechanics, and regular block objects are tested through non-destructive tests such as tension, compression, bending, and impact. It is not suitable for evaluating powder materials. Powder materials usually need to be processed or used in specific scenarios before the strength can be indirectly tested, which undoubtedly increases the difficulty and accuracy of the test. For example, for the strength comparison between porous carbon powders used in lithium-ion batteries (referred to as "lithium batteries") and silicon-carbon composite materials prepared with porous carbon powders, it is usually necessary to make them into negative electrodes and assemble them into batteries to evaluate the relevant electrochemical properties of the batteries before the strength of the two can be obtained.

[0003] At present, there is no unified measurement standard for the mechanical strength of many types of powdered materials. Regarding the strength test of activated carbon, there are standards both internationally and domestically. The international standard is ASTM D 3802 American Standard Ball-Disc Method Strength, and the domestic standard is GB / T 12496.6 Activated Carbon Drum Method Strength. The principle is that the sample is worn by the action of the steel ball, and the ratio of the mass of the material on the sieve to the total mass is the strength value of the activated carbon. The more mass of the material under the sieve, the lower the strength of the material. The disadvantage of this evaluation method is that it cannot guarantee that all samples can be worn by the steel ball, resulting in more material on the sieve and a higher measured strength. In addition, there is also a method of evaluating the mechanical strength of the material by compressive strength, that is, the sample is destroyed by a press, and the force value obtained at the moment of crushing is the compressive strength. CN115911341A proposes a test method for the mechanical strength of porous silicon-carbon negative electrode materials, that is, the material is loaded into a square groove, and the silicon negative electrode material in the groove is squeezed by applying a certain pressure, and the material Dv before and after extrusion is recorded. 10 The change of particle size, the smaller the change of material particle size, the greater the Dv 10 The higher the mechanical strength. However, Dv 10The change is only a macroscopic change in which large particles are crushed into small particles, and cannot reflect the change in the internal structure of the material. CN111477850A proposes a method for testing the mechanical strength of a silicon-carbon precursor material: by applying a certain pressure to the material, a scanning electron microscope is used to observe the structural integrity of the particles under this pressure. However, this method cannot directly quantify the strength of the material and can only reflect the properties of the local material, which is too one-sided and general. CN116864643A proposes to calculate the sphericity of the particles of porous silicon-based negative electrode materials by using the equivalent diameter of the particles by the sedimentation method and the equivalent diameter by the laser diffraction method. High sphericity is beneficial to avoid the crushing and pulverization of particles during rolling, thereby improving the mechanical strength and compaction density. However, the test range of sphericity is limited to regular spherical particles, and cannot show obvious differentiation for irregularly shaped powder materials.

[0004] In summary, previous technologies are unable to directly and effectively quantify the mechanical strength of porous powder materials, and a universally applicable characterization method for the strength of porous powder materials is urgently needed. Summary of the invention

[0005] As mentioned above, there is still a lack of methods that can directly quantify the mechanical strength of powdered porous materials. In response to this problem, the inventors of this application have found through research that when a certain pressure is applied to a powdered porous material with a complex pore structure such as activated carbon, a silicon-carbon composite material based on activated carbon, and then the pressure is removed, the pore structure of the original carbon skeleton will undergo different changes, especially the adsorption specific surface area of ​​the original pore structure will change accordingly. In addition, this measurement of the specific surface area before and after the pressure is applied is closely related to the effect of overcoming the roller pressure stress and the internal expansion stress of the particles in the process of charging and discharging the pole piece in the preparation of the pole piece film layer with the powdered material: the smaller the change caused by the pressure applied to the material and the pressure removed, the stronger its ability to resist the two stresses (rolling pressure stress + expansion stress) after the pole piece is made. The reason is that for porous materials with different resistance stresses, different degrees of carbon skeleton damage will occur under a certain pressure, resulting in different degrees of collapse of the internal pore structure, causing different degrees of irreversible changes in the pore structure and specific surface area of ​​the material. Therefore, by comparing the changes in specific surface area of ​​different powdered porous materials before and after applied pressure, the ability of each powdered material to resist stress can be reflected, which can be directly used to quantify the mechanical strength of the powdered porous material, and then make this strength characterization method suitable for rapid evaluation of the cycle stability of powdered negative electrode materials for lithium batteries.

[0006] To this end, in a first aspect, the present application provides a method for characterizing the mechanical strength of a powdery porous material, comprising: quantifying the mechanical strength by obtaining the specific surface modulus of the powdery porous material;

[0007] The specific modulus is calculated according to the following formula:

[0008] γ(p) = p / ε(p) Formula I

[0009] ε(p)=|S(p)-S(p0)| / S(p0) Formula II; wherein,

[0010] γ(p)—Specific modulus of the material after pressure p is applied to it and then the pressure is removed and restored to normal pressure p0;

[0011] p—pressure applied to the material;

[0012] ε(p)—the rate of change of specific surface area before and after the material is subjected to pressure p;

[0013] S(p0)—Specific surface area of ​​the material before pressure p is applied;

[0014] S(p)—the specific surface area of ​​the material after the pressure p is applied to the material and the pressure is removed;

[0015] The mechanical strength can reflect the ability of the powdery porous material to resist rolling stress and expansion stress in lithium battery applications. For the same type of materials, the higher the specific modulus, the greater the mechanical strength of the powdery porous material.

[0016] This application proposes the concept of "specific modulus" to characterize the mechanical strength of powdered porous materials, which can reflect the ability of the powdered materials to resist rolling stress when preparing lithium batteries and expansion stress during the charging and discharging of lithium batteries. This characterization method is simple to operate and does not require the porous powder materials to be processed into shapes or made into lithium batteries. It is of great significance for quickly evaluating the application performance of powdered porous materials in lithium batteries.

[0017] In some embodiments of the present application, the powdery porous material is a porous carbon material or a silicon-carbon composite material made of a porous carbon material.

[0018] In some embodiments of the present application, the pore structure of the porous carbon material includes micropores and mesopores.

[0019] In some embodiments of the present application, the porous carbon material includes coconut shell carbon, capacitor carbon or carbon aerogel.

[0020] In some embodiments of the present application, the silicon-carbon composite material is formed by depositing silicon and then coating the porous carbon material with carbon.

[0021] In some embodiments of the present application, a powder resistance tester is used to apply pressure to the powdery porous material.

[0022] In some embodiments of the present application, the operation of obtaining the specific modulus includes the following steps:

[0023] S1. Testing the specific surface area of ​​the powdered porous material before applying pressure to obtain the specific surface area S(p0);

[0024] S2, using a powder resistance tester to apply pressure p to the powdery porous material, after compaction, stay for a period of time, and recover the compacted sample;

[0025] S3. Testing the specific surface area of ​​the compacted sample to obtain the specific surface area S(p);

[0026] S4. According to Formula I and Formula II, the specific modulus value γ(p) is calculated.

[0027] In some embodiments of the present application, the applied pressure p is such that the change rate ε(p) of the specific surface area of ​​the powdery porous material before and after the pressure is applied is not less than 0.1%.

[0028] In some embodiments of the present application, in step S2, the applied pressure p is 150-250 MPa, and the residence time is 10-60 s.

[0029] In a second aspect, the present application provides the application of the method for characterizing the mechanical strength of the powdered porous material described in the first aspect in the rapid evaluation of the cycle stability of lithium battery negative electrode materials, wherein the powdered porous material is used as a negative electrode material precursor or as a negative electrode material.

[0030] As mentioned above, the specific modulus can be related to the mechanical strength of the powdered porous material against the rolling stress in the preparation of the pole piece and the internal expansion stress of the particles during the charge and discharge process. Using the specific modulus to evaluate the cycle stability of the negative electrode material can save the tedious operation of preparing the pole piece and assembling the battery and then evaluating it, significantly shorten the evaluation cycle, and efficiently evaluate the impact of the negative electrode material such as silicon-carbon composite materials on the electrochemical cycle performance of lithium batteries, providing guidance for the rapid screening of suitable negative electrode materials.

[0031] In some embodiments of the present application, the powdery porous material is a porous carbon material, and the porous carbon material is used as a precursor of a negative electrode material. The application includes:

[0032] 1) providing a plurality of porous carbon materials;

[0033] 2) obtaining the specific surface modulus of each porous carbon material under the same applied pressure condition;

[0034] 3) Comparing the cycle stability of the negative electrode material based on the specific modulus; the negative electrode material is a silicon-carbon composite material prepared from various porous carbon materials.

[0035] The specific modulus is used to characterize the mechanical strength of each porous carbon material, which can be used to preliminarily judge the ability of the corresponding negative electrode material (silicon-carbon composite material) prepared therefrom to resist rolling stress, and to preliminarily screen out porous carbon materials with high mechanical strength to prepare the silicon-carbon composite material required subsequently.

[0036] In some embodiments of the present application, the powdery porous material is a silicon-carbon composite material, and the silicon-carbon composite material is used as a negative electrode material. The application includes:

[0037] 1) providing a plurality of silicon-carbon composite materials;

[0038] 2) obtaining the specific surface modulus of each silicon-carbon composite material under the same applied pressure condition;

[0039] 3) Compare the cycle stability of the negative electrode materials according to the specific modulus.

[0040] By evaluating the mechanical strength of each silicon-carbon composite material by specific modulus, the operation of preparing all silicon-carbon composite materials into pole pieces and assembling batteries can be omitted.

[0041] In some embodiments of the present application, the application includes:

[0042] a) providing a sample to be tested and a standard sample of the same material type, wherein the standard sample refers to a powdered porous material that can meet the requirements of lithium battery cycle stability;

[0043] b) Under the same applied pressure, obtain the specific modulus γ of the standard sample s and the specific modulus γ of the sample to be tested d ;

[0044] c) Evaluate the cyclic stability of the samples to be tested:

[0045] If (1+c)×γ d <γ s , then the cyclic stability of the sample to be tested is lower than that of the standard sample;

[0046] If (1-c)×γ d >γ s , the cyclic stability of the sample to be tested is higher than that of the standard sample;

[0047] If (1±c)×γ d =γ s , then the cyclic stability of the sample to be tested is equivalent to the cyclic stability of the sample to be tested; where c represents the error rate, which is 5% to 10%.

[0048] When the powdered porous materials are of the same type (for example, all are porous carbon materials or all are silicon-carbon composite materials), by using the material that meets the requirements of cycle stability as the standard sample and comparing it with the specific modulus of the sample to be tested, the materials can be preliminarily screened, eliminating the need to make batteries with all the sample materials to be tested and then test the electrochemical performance. In this way, the rapid evaluation of the cycle stability of the negative electrode material battery can be achieved simultaneously in the process of characterizing the mechanical strength.

[0049] In some embodiments of the present application, the sample to be tested and the standard sample are both porous carbon materials, and the specific modulus of the standard sample at 180 MPa is not less than 10 5 MPa.

[0050] In some embodiments of the present application, the sample to be tested and the standard sample are both silicon-carbon composite materials, and the specific modulus of the standard sample at 160 MPa is not less than 10 4 MPa.

[0051] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0053] Figure 1 Schematic diagram of the operational process for obtaining the specific surface modulus of powdered porous materials in some embodiments. DETAILED DESCRIPTION

[0054] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.

[0055] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0056] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0057] The first aspect of the present application provides a method for characterizing the mechanical strength of a powdery porous material, the method comprising: quantifying the mechanical strength by obtaining the specific surface modulus of the powdery porous material, wherein the mechanical strength can reflect the ability of the powdery porous material to resist rolling stress and expansion stress in lithium battery applications, and for materials of the same type, the higher the specific surface modulus, the greater the mechanical strength of the powdery porous material.

[0058] In this application, "specific surface modulus" is similar to the modulus concept in traditional mechanics and is calculated based on specific surface area data according to the following formula:

[0059] γ(p) = p / ε(p) Formula I

[0060] ε(p)=|S(p)-S(p0)| / S(p0) Formula II; wherein,

[0061] γ(p)—Specific modulus of the material after pressure p is applied to it and then the pressure is removed and restored to normal pressure p0;

[0062] p—pressure applied to the material;

[0063] ε(p)—the rate of change of specific surface area before and after the material is subjected to pressure p;

[0064] S(p0)—Specific surface area of ​​the material before pressure p is applied;

[0065] S(p) - the specific surface area of ​​the material after pressure p is applied to the material and the pressure is removed.

[0066] In the present application, the powdery porous material may be a powder material whose microstructure is based on interconnected or closed pores and has abundant micro- and mesopores on the surface and inside of the particles.

[0067] In some embodiments, the powdery porous material is a porous carbon material or a silicon-carbon composite material made of a porous carbon material.

[0068] In some embodiments, the pore structure of the porous carbon material may include micropores and mesopores.

[0069] In the present application, the porous carbon material may be a pure carbon material. According to some embodiments, the porous carbon material includes at least one of coconut shell carbon, capacitor carbon and carbon aerogel.

[0070] The present application does not particularly limit the source of the porous carbon material, for example, it can be various known commercial products, specific examples include but are not limited to, coconut shell carbon (HA) of Fujian Yuanli, SPC series capacitor carbon of Xinsen Carbon Industry, CQ series carbon aerogel of China Metallurgical Engineering Institute, etc.; it can also be prepared by methods well known in the art.

[0071] In the present application, the silicon-carbon composite material may be formed by compounding a powdered porous carbon material with a silicon element. For example, the silicon-carbon composite material may be obtained by depositing silicon on the porous carbon material and optionally performing carbon coating (with or without carbon coating). The specific preparation method is well known in the art and will not be described in detail herein.

[0072] Furthermore, the silicon-carbon composite material is formed by depositing silicon and coating carbon on the porous carbon material.

[0073] In the present application, the particle size of the powdery porous material may generally range from 0.1 to 30 μm.

[0074] In the present application, the same type of powdered porous materials can be classified at least according to the basic composition of the material and its application method. For example, when the materials have basically the same composition and the same application method, they can be regarded as the same type of materials. For example, porous carbon materials such as coconut shell carbon, capacitor carbon, and carbon aerogel belong to the same type of materials. This is because these carbon materials have basically the same composition and can all be used as precursors of negative electrode materials; further, the same porous carbon material with different pore structures (such as coconut shell carbon with different specific surface areas) can also be regarded as the same type of materials. Silicon-carbon composite materials and porous carbon materials do not belong to the same type of materials: the two have obvious differences in composition and different applications (silicon-carbon composite materials as negative electrode materials).

[0075] In some embodiments, a powder resistance tester is used to apply pressure to the powdered porous material.

[0076] In the present application, in order to obtain the above-mentioned specific surface modulus, it is necessary to accurately measure the two specific surface areas of the powdered porous material before and after the pressure p is applied. In some embodiments, the pore structure of the porous powdered material is composed of a large number of micropores (pore size less than 2nm) and mesopores (pore size 2-50nm) and a small number of macropores (pore size 2-10nm). Preferably, the isothermal adsorption / desorption curve of the adsorption / desorption gas of the material is statically measured, and the BET multi-point method model is used to calculate its specific surface area, and the specific operation method is shown in the following examples.

[0077] In some embodiments, the initial specific surface area of ​​the porous carbon material (ie, S(p0)) is not less than 1000 m 2 / g, the initial specific surface area of ​​the silicon-carbon composite material is not greater than 160m 2 / g.

[0078] In the present application, the pressure p applied to the material can be selected according to the type of powdery porous material to be tested, and the applied pressure should be sufficient to cause an irreversible change in the specific surface area of ​​the powdery porous material. Generally, the pressure p applied to the material should be significantly greater than the rolling pressure used in preparing the negative electrode sheet, and the applied pressure p is preferably more than 5 times the rolling pressure.

[0079] In the present application, in order to ensure that the specific surface area of ​​the material changes effectively after the pressure p is applied, it is preferred that the powdered porous material is compacted and then maintained at the pressure for a certain period of time, for example, 10 to 120 seconds.

[0080] In some embodiments, the applied pressure p is such that the change rate ε(p) of the specific surface area of ​​the material before and after the pressure is applied is not less than 0.1%, thereby reducing the test error.

[0081] It can be understood that when the applied pressure p makes the specific surface area change rate ε(p) before and after compaction < 0.1%, the pressure p can be adjusted until ε(p) ≥ 0.1%. Generally, for the same powdery porous material to be tested, as the applied pressure p increases, the obtained ε(p) increases.

[0082] According to some embodiments, Figure 1 As shown, the operation of obtaining the specific modulus includes the following steps:

[0083] S1. Testing the specific surface area of ​​the powdered porous material before applying pressure to obtain the specific surface area S(p0);

[0084] S2, using a powder resistance tester to apply pressure p to the powdery porous material, after compaction, stay for a period of time, and recover the compacted sample;

[0085] S3. Testing the specific surface area of ​​the compacted sample to obtain the specific surface area S(p);

[0086] S4. According to Formula I and Formula II, the specific modulus value γ(p) is calculated.

[0087] Furthermore, the operation process of step S2 includes: filling the powdery porous material into the carrier mold, setting the target pressure value p in the powder resistance tester, observing the change of the powder resistance during the pressurization process, and when the powder resistance change approaches 0, the material is considered to be completely compacted; continue to maintain the pressure for 10 to 60 seconds (for example, 10 seconds, 20 seconds, 30 seconds, 40 seconds, etc.), and then remove the pressure.

[0088] In some embodiments, the applied pressure p is 150-250 MPa, for example, 150 MPa, 160 MPa, 180 MPa, 190 MPa, 200 MPa, etc.

[0089] The second aspect of the present application provides an application of the method for characterizing the mechanical strength of the powdery porous material described in the first aspect in rapidly evaluating the cycle stability of a negative electrode material for a lithium battery, wherein the powdery porous material is used as a negative electrode material precursor or as a negative electrode material. The mechanical strength characterization method of the present application can be used to rapidly predict the cycle stability of the negative electrode material on a lithium battery.

[0090] In some embodiments, the powdered porous material is a porous carbon material, and the porous carbon material is used as a precursor of a negative electrode material, and the application includes:

[0091] 1) providing a plurality of porous carbon materials;

[0092] 2) obtaining the specific surface modulus of each porous carbon material under the same applied pressure condition;

[0093] 3) Comparing the cycle stability of the negative electrode material based on the specific modulus; wherein the negative electrode material is a silicon-carbon composite material prepared from various porous carbon materials.

[0094] In some other embodiments, the powdery porous material is a silicon-carbon composite material, and the silicon-carbon composite material is used as a negative electrode material. The application includes:

[0095] 1) providing a plurality of silicon-carbon composite materials;

[0096] 2) obtaining the specific surface modulus of each silicon-carbon composite material under the same applied pressure condition;

[0097] 3) Compare the cycle stability of the negative electrode materials according to the specific modulus.

[0098] In some embodiments, the application method includes:

[0099] a) providing a sample to be tested and a standard sample of the same material type, wherein the standard sample refers to a porous powder material that can meet the requirements of lithium battery cycle stability;

[0100] b) Under the same applied pressure, obtain the specific modulus γ of the standard sample s and the specific modulus γ of the sample to be tested d ;

[0101] c) Evaluate the cyclic stability of the samples to be tested:

[0102] If γ s >(1+c)×γ d, then the cyclic stability of the sample to be tested is lower than that of the standard sample;

[0103] If γ s <(1-c)×γ d , the cyclic stability of the sample to be tested is higher than that of the standard sample;

[0104] If γ s =(1±c)×γ d , then the cyclic stability of the sample to be tested is equivalent to the cyclic stability of the sample to be tested; where c represents the error rate, which is 5% to 10%.

[0105] In these embodiments, a material that can meet the cycle stability requirements of a lithium battery is used as a standard sample, and the specific modulus of the sample to be tested is compared with the specific modulus of the standard sample, so that samples that do not meet the use requirements can be initially screened out, eliminating the operation of making the sample to be tested into a battery and then testing the performance. It can be understood that when the sample to be tested and the standard sample are both porous carbon materials, being able to meet the cycle stability means that the silicon-carbon composite material prepared using the standard sample as a precursor meets the cycle stability of the lithium battery.

[0106] In some embodiments, the sample to be tested and the standard sample are both porous carbon materials, and the specific modulus of the standard sample at 180 MPa is not less than 10 5 MPa.

[0107] In other embodiments, the sample to be tested and the standard sample are both silicon-carbon composite materials, and the specific modulus of the standard sample at 160 MPa is not less than 10 4 MPa.

[0108] The application provided in the present application can be used to quickly evaluate the application performance of multiple negative electrode materials of the same type in lithium-ion batteries. The results are compared with the stability evaluation results of lithium batteries made of negative electrode materials. The experimental results of the two are basically consistent, indicating that using the strength characterization method of the present application to evaluate the cyclic stability of negative electrode materials is a reliable and feasible method, and this method also has the advantages of short cycle, simple operation and low cost.

[0109] The following describes embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.

[0110] In the following examples, the isothermal adsorption / desorption curves of the adsorption / desorption gas were measured by the static method using the BSD-660M specific surface area and pore size analyzer, and the specific surface area was calculated using the multi-point BET model, specifically:

[0111] (1) Sample preparation: Take about 0.1 g of the powdered porous material sample to be tested, weigh it, dry it, perform degassing pretreatment, and treat it at 300°C for 8 h;

[0112] (2) Nitrogen adsorption and desorption: After degassing, weigh again and transfer to the nitrogen adsorption and desorption station for testing.

[0113] (3) Data processing: The raw adsorption and desorption data are processed and analyzed according to the model. Among them, the sum of the micropore specific surface area and the surface area is the specific surface area of ​​the powdery porous material.

[0114] A PRCD1100 powder resistor tester (with a pressure operating range of 5 to 200 MPa) from Yuanneng Technology was used to apply pressure to the sample.

[0115] Example 1

[0116] This embodiment is used to test the specific modulus of different porous carbons.

[0117] 1. Provide four types of porous carbon

[0118] Coconut shell carbon, capacitor carbon, and carbon aerogel (all commercially available products) were denoted as porous carbon I, porous carbon II, and porous carbon III, respectively.

[0119] The method for making porous carbon is as follows, wherein parts are parts by weight.

[0120] 4 parts of a mixture of petroleum ether and concentrated hydrochloric acid (the mass ratio of petroleum ether to concentrated hydrochloric acid is 1:0.3) were added to 100 parts of phenolic resin, and the mixture was stirred at 300 rpm for 4 min until the liquid was slightly heated, and the mixed liquid was transferred to a container preheated at 120° C., and placed in a box furnace at 120° C. for activation treatment for 1 h to obtain a primary activation product A1;

[0121] The primary activated product A1 was transferred to a wall breaking machine and broken for 20 min, and then transferred to a box furnace for carbonization at 500 °C for 1 h to obtain a carbonized product B1;

[0122] 100 g of carbonized product B1 was ground and mixed with 300 g of flaky potassium hydroxide, and the mixture was transferred to a tube furnace and nitrogen was passed through to maintain an inert gas atmosphere. The tube furnace was heated to 800 ° C at a rate of 5 ° C / min, kept at this temperature for 2 h, and cooled to room temperature to obtain a secondary activation product C1;

[0123] The secondary activation product C1 was immersed in a 1 mol / L hydrochloric acid solution, filtered, and washed with a large amount of water until the pH of the filtrate was neutral. After drying, it was crushed and sieved to obtain a porous carbon material powder, which was recorded as porous carbon IV.

[0124] 2. Specific modulus test

[0125] S1. Perform an initial specific surface area test on each porous carbon to obtain a surface area value S(p0);

[0126] S2. Apply a pressure of 180 MPa to the porous carbon using a powder resistance tester. After compaction, stay for 10 seconds to obtain a compacted sample.

[0127] S3. Take the powder of the compacted sample and perform a specific surface area test to obtain a specific surface area S(p);

[0128] S4. Use the specific modulus calculation formula to obtain the specific modulus value γ(p).

[0129] The test results are shown in Table 1.

[0130] Table 1

[0131]

[0132]

[0133] By comparison, it can be seen that the specific surface modulus of the four porous carbons is: porous carbon IV>porous carbon II>porous carbon I>porous carbon III. It is preliminarily judged that the cycle performance of silicon-carbon negative electrode materials prepared by the same silicon-carbon deposition (silicon deposition + carbon coating) method in lithium-ion batteries is in the following order: porous carbon IV>porous carbon II>porous carbon I>porous carbon III.

[0134] Example 2

[0135] This example is used to test the specific surface modulus of the silicon-carbon composite materials prepared from the four porous carbons in Example 1.

[0136] 1. Provide four kinds of silicon-carbon composite materials

[0137] The porous carbons I to IV were used as negative electrode material precursors, respectively, and silicon-carbon composite materials I to IV were obtained by the following vapor deposition process:

[0138] Silane gas deposition and primary carbon coating are carried out in a fluidized bed. The specific operation method is: first, the fluidized bed is heated from 20°C to T1 (520°C) under a nitrogen atmosphere, and gas replacement is carried out after reaching the temperature. After completion, silane gas is introduced for silane deposition. After the deposition is completed, the temperature is continued to be raised to T2 (580°C) and acetylene is used as the carbon source for primary carbon coating. After the coating is completed, it is naturally cooled to room temperature and discharged. The operating conditions of each process are shown in Table 2 below.

[0139] Table 2

[0140]

[0141] After being discharged from the fluidized bed, secondary carbon coating was carried out in a rotary kiln using acetylene as the carbon source. Specifically, the temperature was raised to 580°C at a rate of 5°C / min under a nitrogen atmosphere, with a nitrogen flow rate of 1.5 L / min, and the temperature was kept for 90 minutes. Finally, the temperature was naturally cooled to room temperature to obtain silicon-carbon composite materials I to IV.

[0142] 2. Specific modulus test

[0143] S1. Performing an initial specific surface area test on each silicon-carbon composite material to obtain a surface area value S(p0);

[0144] S2, applying a pressure of 160 MPa to the silicon-carbon composite material using a powder resistance tester, and after compaction, staying for 30 seconds to obtain a compacted sample;

[0145] S3. Take the powder of the compacted sample and perform a specific surface area test to obtain a specific surface area S(p);

[0146] S4. Use the specific modulus calculation formula to obtain the specific modulus value γ(p).

[0147] The test results are shown in Table 3.

[0148] Table 2

[0149]

[0150]

[0151] It can be seen from Table 3 that the specific modulus values ​​of each silicon-carbon composite material are approximately 10 3 ~10 4 MPa, which is smaller than that of porous carbon. The reason is that the specific surface area of ​​the silicon-carbon composite material is relatively small before pressure is applied (silicon is deposited into the pores of porous carbon to reduce the surface area), and the rate of change of the specific surface area before and after pressure is applied is large, so the specific surface modulus value obtained is small.

[0152] The specific modulus of the porous silicon-carbon composite material is as follows: silicon-carbon composite material IV>silicon-carbon composite material II>silicon-carbon composite material I>silicon-carbon composite material III.

[0153] Reliability Test

[0154] 1. Preparation of lithium-ion batteries

[0155] The above silicon-carbon composite materials were used as negative electrode materials to make button cells for testing.

[0156] Weigh 0.96 g of silicon-carbon composite material (active material), and weigh the corresponding proportion of slurry materials according to the slurry ratio (mass ratio) of active material: SBR: CMC: SP = 80: 5: 5: 10. Mix them with deionized water to obtain a slurry with a solid content of 25% of the silicon-carbon negative electrode active material and put it into a degassing tank.

[0157] The slurry was degassed in a degassing machine for 4 times, and the single degassing mode was: degassed at 850 rpm for 1 minute and then degassed at 2000 rpm for 12 minutes, thereby obtaining a mixed uniform slurry;

[0158] The mixed slurry is coated on 8 μm double-sided copper foil using a 75 μm scraper, and the speed of the coating machine is fixed;

[0159] Pole drying and cutting: Place the coated pole piece in an 80°C oven for 2 hours, then place it in a vacuum oven for 12 hours, weigh and record the dried pole piece;

[0160] Button cell assembly: The dried electrode and counter electrode (lithium sheet), electrolyte (1M LiPF6, solvent DEC:EC=1:1, v / v), and PE porous diaphragm are placed in a glove box for button cell assembly.

[0161] 2. Cycle performance test

[0162] The assembled button cell was tested on a battery testing system with a test voltage range of 0.005V to 1.5V. It was discharged to 0.01V at a constant current of 0.1C, then deeply discharged to 0.005V at a constant current of 0.01C, and then charged to 1.5V at a constant current of 0.1C. The charged capacity was divided by the mass of the active substance (negative electrode material) to obtain the charged gram capacity (reversible gram capacity) of the negative electrode material. The battery was charged and discharged in a cycle using the above discharge-charge procedure. The ratio of the reversible gram capacity of the 50th cycle to the reversible gram capacity of the first cycle is the cycle capacity retention rate.

[0163] The test results are shown in Table 4.

[0164] Table 4

[0165] Serial number First cycle reversible gram capacity, mAh / g 50 cycle capacity retention rate, % Silicon Carbon Composite Material I 1618.28 58.64 Silicon Carbon Composite Material II 1839.84 60.81 Silicon Carbon Composite Material III 1208.43 40.39 Silicon Carbon Composite Material IV 2354.17 61.37

[0166] As can be seen from Table 4, after assembling to form a battery, the cycle stability of the four silicon-carbon composite materials as negative electrode materials for lithium-ion batteries is ranked as follows: silicon-carbon composite material IV>silicon-carbon composite material II>silicon-carbon composite material I>silicon-carbon composite material III, which is consistent with the comparison result of the specific surface modulus and the comparison result of the specific surface modulus of the corresponding porous carbon in Example 1. It can be seen that by comparing the specific surface moduli of multiple activated carbons, the cycle stability of the silicon-carbon composite materials (as negative electrode materials) prepared by the same process can be quickly evaluated.

[0167] Evaluation significance: On the one hand, when it is necessary to verify the mechanical strength of different powdered porous carbons and the cycle stability of silicon-carbon composites prepared from porous carbon, there is no need to assemble the silicon-carbon composites into batteries. It is only necessary to test the specific modulus of the precursor porous carbon. By comparing the specific modulus, the mechanical strength of each material can be directly quantified and its cycle stability as a negative electrode material can be preliminarily evaluated. On the other hand, porous carbon IV can be used as a standard sample, and various other porous carbons (such as other commercially available resin-based porous carbons) can be used as test samples to test their specific modulus. By comparing the specific modulus of other porous carbons with that of porous carbon IV, porous carbon materials suitable for silane vapor deposition can be preliminarily screened out.

[0168] In summary, the present application can directly quantify the mechanical strength of powdered porous materials by using specific modulus, and by comparing multiple porous carbon materials or multiple silicon-carbon composite materials, the cycle stability of the corresponding negative electrode material can be quickly and reliably evaluated.

[0169] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A method for characterizing the mechanical strength of a powdery porous material, characterized in that: include: The mechanical strength is quantified by obtaining the specific modulus of the powdery porous material, which is calculated according to the following formula: γ(p) = p / ε(p) Formula I ε(p)=|S(p)-S(p0)| / S(p0) Formula II; wherein, γ(p)—Specific modulus of the material after pressure p is applied to it and then the pressure is removed and restored to normal pressure p0; p—pressure applied to the material; ε(p)—the rate of change of specific surface area before and after the material is subjected to pressure p; S(p0)—Specific surface area of ​​the material before pressure p is applied; S(p)—the specific surface area of ​​the material after the pressure p is applied to the material and the pressure is removed; The mechanical strength can reflect the ability of the powdery porous material to resist rolling stress and expansion stress in lithium battery applications. For the same type of materials, the higher the specific modulus, the greater the mechanical strength of the powdery porous material.

2. The characterization method according to claim 1, characterized in that The powdery porous material is a porous carbon material or a silicon-carbon composite material made of a porous carbon material; Preferably, the pore structure of the porous carbon material includes micropores and mesopores; Preferably, the porous carbon material comprises coconut shell carbon, capacitor carbon or carbon aerogel; Preferably, the silicon-carbon composite material is formed by depositing silicon and coating carbon on the porous carbon material.

3. The characterization method according to claim 1 or 2, characterized in that: A powder resistance tester is used to apply pressure to the powdery porous material.

4. The characterization method according to any one of claims 1 to 3, characterized in that: The operation of obtaining the specific modulus comprises the following steps: S1. Testing the specific surface area of ​​the powdered porous material before applying pressure to obtain the specific surface area S(p0); S2, using a powder resistance tester to apply pressure p to the powdery porous material, after compaction, stay for a period of time, and recover the compacted sample; S3. Testing the specific surface area of ​​the compacted sample to obtain the specific surface area S(p); S4. According to Formula I and Formula II, the specific modulus value γ(p) is calculated.

5. The characterization method according to claim 4, characterized in that: The applied pressure p is such that the rate of change ε(p) of the specific surface area of ​​the powdery porous material before and after the pressure is applied is not less than 0.1%; Preferably, in step S2, the applied pressure p is 150-250 MPa, and the residence time is 10-60 s.

6. Application of the method for characterizing the mechanical strength of a powdery porous material according to any one of claims 1 to 5 in rapidly evaluating the cycle stability of a negative electrode material for a lithium battery, wherein: The powdery porous material is used as a negative electrode material precursor or as a negative electrode material.

7. The use according to claim 6, characterized in that: The powdery porous material is a porous carbon material, and the porous carbon material is used as a precursor of a negative electrode material. The application includes: 1) providing a plurality of porous carbon materials; 2) obtaining the specific surface modulus of each porous carbon material under the same applied pressure condition; 3) Comparing the cycle stability of the negative electrode material based on the specific modulus; wherein the negative electrode material is a silicon-carbon composite material prepared from various porous carbon materials.

8. The use according to claim 6, characterized in that: The powdery porous material is a silicon-carbon composite material, and the silicon-carbon composite material is used as a negative electrode material. The application includes: 1) providing a plurality of silicon-carbon composite materials; 2) obtaining the specific surface modulus of each silicon-carbon composite material under the same applied pressure condition; 3) Compare the cycle stability of the negative electrode materials according to the specific modulus.

9. The use according to claim 6, characterized in that: The app includes: a) providing a sample to be tested and a standard sample of the same material type, wherein the standard sample refers to a powdered porous material that can meet the requirements of lithium battery cycle stability; b) Under the same applied pressure, obtain the specific modulus γ of the standard sample s and the specific modulus γ of the sample to be tested d ; c) Evaluate the cyclic stability of the samples to be tested: If (1+c)×γ d <γ s , then the cyclic stability of the sample to be tested is lower than that of the standard sample; If (1-c)×γ d >γ s , then the cyclic stability of the sample to be tested is higher than that of the standard sample; If (1±c)×γ d =γ s , then the cyclic stability of the sample to be tested is equivalent to the cyclic stability of the sample to be tested; where c represents the error rate, which is 5% to 10%.

10. The use according to claim 9, characterized in that: The sample to be tested and the standard sample meet one of the following conditions: The sample to be tested and the standard sample are both porous carbon materials, and the specific modulus of the standard sample at 180 MPa is not less than 10 5 MPa; The sample to be tested and the standard sample are both silicon-carbon composite materials, and the specific modulus of the standard sample at 160 MPa is not less than 10 4 MPa.

Citation Information

Patent Citations

  • High-compaction silicon-carbon negative electrode precursor material, preparation method thereof and prepared high-compaction silicon-carbon negative electrode material

    CN111477850A

  • Porous silicon carbon negative electrode material, preparation method and application

    CN115911341A

  • Silicon-based composite material, preparation method and battery

    CN116864643A